Determinants of Fintech Application Usage with Interest as a Mediating Variable among Gen-Z in the Jabodetabek Area - Wijaya, Denny; Medyawati, Henny (Dinasti Publisher, 2026)
The rapid advancement of digital technology has accelerated the widespread adoption of financial technology (fintech) services, notably the GoPay digital wallet, which maintains a dominant position in the Indonesian e-wallet market. Despite its high penetration, the continuous usage of GoPay among Generation Z remains contingent upon perceived benefits and user trust, particularly concerning personal data security. This study aims to analyze the impact of performance expectancy and trust on the usage of the GoPay application among Generation Z in the Greater Jakarta (Jabodetabek) area, both directly and as mediated by behavioral intention. A quantitative research design was employed, involving the distribution of questionnaires to 400 Generation Z respondents who are familiar with GoPay but are not yet intensive users. Employing Structural Equation Modeling-Partial Least Squares (SEM-PLS) as the analytical framework, this study finds that performance expectancy, trust, and behavioral intention significantly influence GoPay application usage. Notably, performance expectancy does not transmit a significant indirect effect on usage through behavioral intention. By contrast, trust exerts a significant mediated effect on usage, with behavioral intention functioning as an intervening variable in this relationship.